Broad-spectrum anti-HIV activity and high drug resistance barrier of lipopeptide HIV fusion inhibitor LP-19 - He, Lin; Wang, Chen; Zhang, Yuanyuan; Chong, Huihui; Hu, Xiaoyan; Li, Dan; Xing, Hui; He, Yuxian; Shao, Yiming; Hong, Kunxue; Ma, Liying (Frontiers in Immunology, 2023)
Lipopeptide-19, a HIV fusion inhibitor (LP-19), has showed potent anti-HIV activity. However, there is still limited information of the antiviral activity against different subtype clinical isolates and the drug resistance barrier of LP-19. Therefore, 47 HIV clinical isolates were selected for this study. The viral features were identified, in which 43 strains are CCR5 tropisms, and 4 strains are CCR5/CXCR4 tropisms, and there are 6 subtype B’, 15 CRF01_AE, 14 CRF07_BC, 2 CRF08_BC and 10 URF strains. These 47 viruses were used to detected and analyze the inhibitory activities of LP-19. The results showed that the average 50% inhibitory concentration (IC50) and 90% inhibitory concentration (IC90) of LP-19 were 0.50 nM and 1.88 nM, respectively. The average IC50 of LP-19 to B’, CRF01_AE, CRF07_BC, CRF08_BC, and URF strains was 0.76 nM, 0.29 nM, 0.38 nM, 0.85 nM, and 0.44 nM, respectively. C34 and Enfuvirtide (T-20), two fusion inhibitors, were compared on the corresponding strains simultaneously. The antiviral activity of LP-19 was 16.7-fold and 86-fold higher than that of C34 and T-20. The antiviral activity of LP-19, C34, and T-20 were further detected and showed IC50 was 0.15 nM, 1.02 nM, and 66.19 nM, respectively. IC50 of LP-19 was about 7-fold and 441-fold higher compared to C34 and T-20 against HIV-1 NL4-3 strains. NL4-3 strains were exposed to increasing concentrations of LP-19 and C34 in MT-2 cell culture. The culture virus was sequenced and analyzed. The results showed that A243V mutation site identified at weeks 28, 32, 38, and 39 of the cell culture in the gp41 CP (cytoplasmic domain) region. NL4-3/A243V viruses containing A243V mutation were constructed. Comparing the antiviral activities of LP-19 against HIV NL4-3 to HIV strains (only 1.3-fold), HIV did not show drug resistance when LP-19 reached 512-fold of the initial concentration under the drug pressure for 39 weeks. This study suggests that LP-19 has broad-spectrum anti-HIV activity, and high drug resistance barrier.